2010
DOI: 10.1128/jcm.00529-10
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis Caused by Escherichia coli Producing TEM-52 Extended-Spectrum β-Lactamase within an Extensive Outbreak in a Neonatal Ward: Epidemiological Investigation and Characterization of the Strain

Abstract: Outbreaks caused by Enterobacteriaceae isolates producing extended-spectrum ␤-lactamases (ESBL) in neonatal wards can be difficult to control. We report here an extensive outbreak in a neonatal ward with a case of meningitis caused by an ESBL-producing Escherichia coli strain. Between 24 March and 29 April 2009, among the 59 neonates present in the ward, 26 neonates with ESBL-producing E. coli rectal colonization were detected (44%). One of the colonized neonates developed meningitis with a favorable outcome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 35 publications
1
66
0
1
Order By: Relevance
“…Most of the virulence-associated traits of isolates belonging to ST88 were adhesins, protectins, and siderophores that may facilitate persistence and survival in adverse circumstances. Phylogroup C has previously been identified in a virulent strain causing an outbreak in a neonatal ward (37). Interestingly, in this study, 30% of E. coli isolates belonged to phylogroup C, mainly due to the reclassification of prevalent clonal complexes ST10 and ST23 (Table 2) previously classified as phylogroup A by the former method of Clermont et al (19).…”
Section: Discussionmentioning
confidence: 68%
“…Most of the virulence-associated traits of isolates belonging to ST88 were adhesins, protectins, and siderophores that may facilitate persistence and survival in adverse circumstances. Phylogroup C has previously been identified in a virulent strain causing an outbreak in a neonatal ward (37). Interestingly, in this study, 30% of E. coli isolates belonged to phylogroup C, mainly due to the reclassification of prevalent clonal complexes ST10 and ST23 (Table 2) previously classified as phylogroup A by the former method of Clermont et al (19).…”
Section: Discussionmentioning
confidence: 68%
“…The emergence of ESBL-producing strains needs to be closely monitored in the future, considering its potential impact on the choice of empirical therapy. Outbreaks of ESBL-producing E. coli strains on neonatal intensive care units did not occur during the study period, but have recently been reported from elsewhere in Europe [8,9].…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, the increase in genome research and multi-locus sequence data put forward eight new phylo-groups of E. coli, assigned as A, B1, B2, C, D, E and F which belong to E. coli sensu stricto and one correspond to the Escherichia cryptic clade I (Jaureguy et al 2008;Moissenet et al 2010;Tenaillon et al 2010;Clermont et al 2011;Luo et al 2011). Group E is recognized as a new group that was formerly comprised unassigned strains; group F designated as sister group of B2; group C includes strains closely related but distinct from group B1 and an Escherichia clade I which is considered to be a new phylo-group that is phenotypically indistinguishable but genotypically different from E. coli (Clermont et al 2013).…”
Section: Introductionmentioning
confidence: 99%